Practical issues in the measurement of child survival in health systems trials: experience developing a digital community-based mortality surveillance programme in rural Nepal. Issue 4 (19th December 2016) - Harsha Bangura, Alex; Ozonoff, Al; Citrin, David; Thapa, Poshan; Nirola, Isha; Maru, Sheela; Schwarz, Ryan; Raut, Anant; Belbase, Bishal; Halliday, Scott; Adhikari, Mukesh; Maru, Duncan
Abstract : Child mortality measurement is essential to the impact evaluation of maternal and child healthcare systems interventions. In the absence of vital statistics systems, however, assessment methodologies for locally relevant interventions are severely challenged. Methods for assessing the under-5 mortality rate for cross-country comparisons, often used in determining progress towards development targets, pose challenges to implementers and researchers trying to assess the population impact of targeted interventions at more local levels. Here, we discuss the programmatic approach we have taken to mortality measurement in the context of delivering healthcare via a public–private partnership in rural Nepal. Both government officials and the delivery organisation, Possible, felt it was important to understand child mortality at a fine-grain spatial and temporal level. We discuss both the short-term and the long-term approach. In the short term, the team chose to use the under-2 mortality rate as a metric for mortality measurement for the following reasons: (1) as overall childhood mortality declines, like it has in rural Nepal, deaths concentrate among children under the age of 2; (2) 2-year cohorts are shorter and thus may show an impact more readily in the short term of intervention trials; and (3) 2-year cohorts are smaller, making prospective census cohorts more feasible in small populations. In the long term, Possible developed a digital continuous surveillance system to capture deaths as they occur, at which point under-5 mortality assessment would be desirable, largely owing to its role as a global standard.